A statistical approach for selecting buildings for experimental measurement of HVAC Leeds = Statystyczna metoda wyboru budynków badawczych na potrzeby analizy systemów HVAC - Malinowski, Paweł; Ziembicki, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article presents a statistical methodology for selecting representative buildings for experimentally evaluating the performance of HVAC systems, especially in terms of energy consumption. The proposed approach is based on the k-means method.
Keywords: k-means method; HVAC system performance; energy consumption; building characteristics; metoda k-średnich; systemy HVAC; zużycie energii; charakterystyka energetyczna budynku